Genome‐Wide Association Mapping of Leaf Rust Response in a Durum Wheat Worldwide Germplasm Collection. Issue 3 (1st November 2016) - Aoun, Meriem; Breiland, Matthew; Kathryn Turner, M.; Loladze, Alexander; Chao, Shiaoman; Xu, Steven S.; Ammar, Karim; Anderson, James A.; Kolmer, James A.; Acevedo, Maricelis
Abstract : Leaf rust (caused by Puccinia triticina Erikss. [ Pt ]) is increasingly impacting durum wheat ( Triticum turgidum L. var. durum ) production with the recent appearance of races with virulence to widely grown cultivars in many durum producing areas worldwide. A highly virulent P. triticina race on durum wheat was recently detected in Kansas. This race may spread to the northern Great Plains, where most of the US durum wheat is produced. The objective of this study was to identify sources of resistance to several races from the United States and Mexico at seedling stage in the greenhouse and at adult stage in field experiments. Genome‐wide association study (GWAS) was used to identify single‐nucleotide polymorphism (SNP) markers associated with leaf rust response in a worldwide durum wheat collection of 496 accessions. Thirteen accessions were resistant across all experiments. Association mapping revealed 88 significant SNPs associated with leaf rust response. Of these, 33 SNPs were located on chromosomes 2A and 2B, and 55 SNPs were distributed across all other chromosomes except for 1B and 7B. Twenty markers were associated with leaf rust response at seedling stage, while 68 markers were associated with leaf rust response at adult plant stage. The current study identified a total of 14 previously uncharacterized loci associated with leaf rust response in durum wheat. The discovery of these loci through association mapping (AM) is a significant step in identifying useful sources of resistance that can be used to broaden the relatively narrow leaf rust resistance spectrum in durum wheat germplasm.